Asghar Ali Engineer's Concept On Women Liberation (An Islamic Response) - Rasyidah, Hasna Safarina, Dr. Syamsul Hidayat, M.Ag, Drs. Suharjianto, M.Ag (2015)
It is something natural, when women argue their ideas to liberate their selves to be treated equally like men did. It might be self-defense from the oppression they saw, from the limitation they had because they are the object itself. But how did men see this thing? This is one reason, why this research is limited on Asghar Ali Engineer (India, 1939-now) as one of male feminists who is also a reformist thinker of the contemporary Muslim world. He paid his great attention to the question of women liberation such as: equality, marital rights, concept of jilbab, and women as head of state while some answers are afforded to solve those problems above, based on the interpretation of Qur'an taken from Tafsir al Mishbah written by M. Quraish Shihab (Indonesia, 1944-now), which is a interpretation representative to see women liberation from the sight of Islam for it was written in the same era as the thought of women liberation raised. As a qualitative study, this research is based on a pure library research which the collected data is described, and afterwards analyzed and criticized by Islamic framework. Interpretation of Qur'an should pass the right methodology before using ratio and reason, because it was the only way to gain the right concept of every sphere in life. This thesis ended up by conclusion that Engineer's concept of women liberation is dominated by reason which plays a very crucial role in human's life even though in interpreting Qur'anic verses. While Quraish Shihab, even if he lived in the same era as Engineer, and he interpreted Qur'an by ratio, but he passed the right way of using the methodology of understanding Qur'an, not merely using the ratio or reason. He places women in the great position, neither below men's position nor equal with them, because even women or men, have their own portions in living the life.